Validity and Responsiveness of VELO: A Velopharyngeal Insufficiency Quality of Life Measure. Issue 2 (12th April 2013) - Skirko, Jonathan R.; Weaver, Edward M.; Perkins, Jonathan A.; Kinter, Sara; Eblen, Linda; Sie, Kathleen C.Y.
Abstract : Objective: Test the Velopharyngeal Insufficiency (VPI) Effects on Life Outcomes (VELO) instrument for validity, reliability, and responsiveness. Study Design: Observational cohort. Setting: Academic tertiary medical center. Subjects: Children with VPI (n = 59) and their parents (n = 84) were prospectively enrolled from a pediatric VPI clinic. Methods: Pediatric speech language pathologists diagnosed VPI using perceptual speech analysis and rated VPI severity and speech intelligibility deficit (each as minimal, mild, moderate, or severe). All parents and youth 8+ years old (n = 24) completed the VELO instrument and other quality‐of‐life questionnaires at baseline; the first 40 subjects completed the VELO instrument again 2 weeks later. Treatments included Furlow palatoplasty (n = 20), sphincter pharyngoplasty (n = 14), or an obturator (n = 2), and 29 of 36 (81%) subjects completed the questionnaires 3 months posttreatment. VELO was tested with correlations for criterion validity against VPI severity, construct validity against speech intelligibility and velopharyngeal gap size, and concurrent validity against other quality‐of‐life measures ( r >. 40 demonstrating validity); for test‐retest reliability using intraclass correlation (>.6 demonstrating reliability); and for responsiveness with the 3‐month posttreatment measure using the paired t test. Results: Parental responses are reported; youth responses showed similar results. The VELO instrument did not meet criterion validity ( r = –.18, P =. 10), or functional construct validity ( r = –.37, P =. 001), but did meet anatomic construct and concurrent validity (each r >. 50, P <. 01). VELO scores demonstrated excellent test‐retest reliability ( r =. 85, P <. 001) and responsiveness (baseline 54 ± 14 to posttreatment 70 ± 18, P <. 001). Conclusion: VELO provides a VPI‐specific quality‐of‐life instrument that demonstrates concurrent validity, test‐retest reliability, and responsiveness to change in quality of life with treatment.